2010
DOI: 10.1590/s1983-14472010000200021
|View full text |Cite
|
Sign up to set email alerts
|

Perfil dos atendimentos a crianças e adolescentes vítimas de causas externas de morbimortalidade, 2000-2006

Abstract: External causes are important factors of infant morbimortality and permanent impairments around the world. This quantitative, descriptive and cross-sectional study aimed to characterize emergency care for children and adolescents, aged from zero to 19 years old, victims of external causes of morbimortality in a university hospital in the countryside of São Paulo, Brazil, between the years of 2000 and 2006. By the end of the study, researchers found 6302 emergency attendances and most of the reported cases occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
8
0
18

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 15 publications
(27 reference statements)
3
8
0
18
Order By: Relevance
“…3,15,16 The transport accidents obtained a percentage very close to the one of aggressions, this is due to this type of external causes to grow as an important cause of mortality and morbidity in young men. 19 This finding corroborates with those found in the literature that point to transportation accidents followed by aggressions as a major cause of emergency room and hospitalization. 19 In addition to corroborating with several studies that indicated this type of injury as the most frequent 15,19 , the risk behavior for traffic accidents is determined in part by the pressure exerted by a group, by immaturity, by the feeling of omnipotence, by excessive alcohol, high speed and recklessness of the driver.…”
Section: Characteristics Of Deathssupporting
confidence: 91%
See 1 more Smart Citation
“…3,15,16 The transport accidents obtained a percentage very close to the one of aggressions, this is due to this type of external causes to grow as an important cause of mortality and morbidity in young men. 19 This finding corroborates with those found in the literature that point to transportation accidents followed by aggressions as a major cause of emergency room and hospitalization. 19 In addition to corroborating with several studies that indicated this type of injury as the most frequent 15,19 , the risk behavior for traffic accidents is determined in part by the pressure exerted by a group, by immaturity, by the feeling of omnipotence, by excessive alcohol, high speed and recklessness of the driver.…”
Section: Characteristics Of Deathssupporting
confidence: 91%
“…19 This finding corroborates with those found in the literature that point to transportation accidents followed by aggressions as a major cause of emergency room and hospitalization. 19 In addition to corroborating with several studies that indicated this type of injury as the most frequent 15,19 , the risk behavior for traffic accidents is determined in part by the pressure exerted by a group, by immaturity, by the feeling of omnipotence, by excessive alcohol, high speed and recklessness of the driver. 15 Alcohol abuse and disrespect to traffic laws can be pointed out as factors directly related to this type of accident.…”
Section: Characteristics Of Deathssupporting
confidence: 91%
“…To minimize this type of trauma, children must be carefully supervise by their parents, especially when they are in places that offer danger to the occurrence of this type of accident (14) . It is noteworthy that the effective participation of health professionals by means of preventive actions directed to this audience at schools and communities could also minimize accident rates and therefore, they are considered essential (15) . Within this context, it is clear that health professionals in primary care, especially nurses, play a key role in helping prevent home accidents as they can offer educational guidance because they are part of the community.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to the professionals involved in the care of burn patients, it was found that the medical and nursing professionals offered 100% of assistance, followed by psychologists and physiotherapists with 237 and 172 consultations, respectively, and last social assistants (59) and nutritionists (15).…”
Section: Resultsmentioning
confidence: 99%
“…Esta faixa etária encontra-se predisposta a acidentes devido ao rápido crescimento e desenvolvimento, vulnerabilidade e imaturidade das crianças e adolescentes. 23 O sexo masculino é o mais acometido nessa idade, o que pode ser justiicado pelos diferentes comportamentos de cada sexo e pela educação diferenciada, em que os meninos desenvolvem atividades mais vigorosas. 24 Em Pelotas-RS e no Rio Grande do Sul, os óbitos classiicados como decorrentes de outras causas externas tiveram um coeiciente de regressão negativo em menores de 15 anos, em ambos os sexos, sendo que em Pelotas-RS esse decréscimo foi estatisticamente signiicativo.…”
unclassified